The validity of mid-upper arm circumference as an indicator of underweight, overweight and obesity adults in Bangladesh. - Sheikh Arafat Rahman; Md Humayan Kabir; Shaikh Shahinur Rahman; Md Kamruzzaman (PLoS ONE)
Background Mid-upper-arm circumference (MUAC), as a simple measurement, is an effective alternative to body mass index (BMI) for resource-limited countries such as Bangladesh. The present study aimed to investigate the age- and sex-specific MUAC cut-off points as screening tools for underweight, overweight and obesity in Bangladesh. Subject and methods A nationally representative dataset (BDHS-2017/18) comprising of 12,962 adults individuals (females: 56.5%, mean age: 39.5±16.0 Years, BMI: 22.4±4.1 kg/m2 and MUAC: 27.4±3.1 cm) was analyzed. BMI was categorized as underweight (BMI <18.5 kg/m2), overweight (BMI: 23 kg/m2), or obese (BMI: ≥27.5 kg/m2). A receiver operating characteristic curve analysis was conducted to determine the optimal MUAC cut-off, based on Youden Index, for underweight, overweight, and obese individuals. Multiple linear regression analysis was performed, adjusting for age and sex, to explore age and sex-specific changes in the association between MUAC and BMI. Restricted cubic spline and binary logistic regression analyses were performed to evaluate the risk of underweight, overweight and obesity among different MUAC quartiles. Results For males, MUAC cut-offs were ≤26.5 cm for underweight (AUC: 82.1%, sensitivity: 71.1%, specificity: 77.8%), ≥ 28.5 cm for overweight (AUC: 84.8%, sensitivity: 77.6%, specificity: 76.9%), and ≥29.5 cm for obesity (AUC: 89.4%, sensitivity: 87.8%, specificity: 76.6%) in younger and middle-aged individuals; older males had cut-offs of ≤25.5 cm, ≥ 27.5 cm, and ≥29.5 cm respectively. For females, the cut-offs were lower: ≤ 25.5 cm for underweight in younger and middle-aged, and ≤24.5 cm in older; ≥ 27.5 cm for overweight in younger, and ≥26.5 cm in middle-aged and older; and ≥28.5 cm for obesity in younger and middle-aged, and ≥27.5 cm in older. The MUAC-BMI correlation was strong (R = 0.69, P < 0.001), stronger in males (R = 0.75) than females (R = 0.69). The MUAC cut-off for underweight, overweight, and obesity slightly decreased with age in both sexes. Conclusion Age- and sex-specific MUAC cut-offs are effective for screening underweight, overweight and obesity in Bangladesh.